Protective efficacy induced by Eimeria maxima rhomboid-like protein 1 against homologous infection - Wang, Mingyue; Tian, Di; Xu, Lixin; Lu, Mingmin; Yan, Ruofeng; Li, Xiangrui; Song, Xiaokai (Frontiers in Veterinary Science, 2023)
Avian coccidiosis, caused by apicomplexan protozoa belonging to the Eimeria genus, is considered one of the most important diseases in the intensive poultry industry worldwide. Due to the shortcomings of live anticoccidial vaccines and drugs, the development of novel anticoccidial vaccines is increasingly urgent. In this study, Eimeria maxima rhomboid-like protein 1 (EmROM1), an invasion-related molecule, was selected as a candidate antigen to evaluate its protective efficacy against E. maxima in chickens. Firstly, the prokaryotic recombinant plasmid pET-32a-EmROM1 was constructed to prepare EmROM1 recombinant protein (rEmROM1), which was used as a subunit vaccine. The eukaryotic recombinant plasmid pVAX1.0-EmROM1 (pEmROM1) was constructed as a DNA vaccine. Subsequently, 2-week-old chicks were separately vaccinated with the rEmROM1 and pEmROM1 twice every 7 days. One week post the booster vaccination, induced cellular immune responses were determined by evaluating the mRNA level of cytokines including IL-2, IFN-γ, IL-4, IL-10, TGF-β, IL-17, and TNFSF15, as well as the percentages of CD4+ and CD8+ T cells from spleens of vaccinated chickens. Specific serum antibody level in the vaccinated chickens was determined to assess induced humoral immune responses. Finally, the protective efficacy of EmROM1 was evaluated by a vaccination-challenge trial. The results revealed that EmROM1vaccination significantly upregulated the cytokine transcription levels and CD4+ / CD8+ T cell percentages in vaccinated chickens compared with control groups, and also significantly increased the levels of serum-specific antibodies in vaccinated chickens. The animal trial showed that EmROM1 vaccination significantly reduced oocyst shedding, enteric lesions, and weight loss of infected birds compared with the controls. The anticoccidial index (ACI) from the rEmROM-vaccination group and pEmROM1-vaccination group were 174.11 and 163.37, respectively, showing moderate protection against E. maxima infection. Collectively, EmROM1 is an effective candidate antigen for developing DNA or subunit vaccines against avian coccidiosis.